The Influence of E-Wom on Purchase Intention of Mixue Products with Brand Awareness as a Mediating Variable - Mahyuddina Almas; Bambang Irawan; Mochammad Farid (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the influence of electronic word of mouth (e-WOM) specifically its quality, quantity, and credibility on purchase intention, with brand awareness as a mediating variable for Mixue products in Jember Regency. The research employed a quantitative explanatory method using purposive sampling involving 160 respondents. The findings indicate that e-WOM quality, quantity, and credibility significantly influence purchase intention. However, only e-WOM credibility has a significant impact on brand awareness and is proven to mediate the relationship between e-WOM credibility and purchase intention. In contrast, e-WOM quality and quantity do not significantly affect brand awareness, and thus brand awareness does not mediate their relationship with purchase intention. These findings highlight the importance of information credibility in building brand awareness and enhancing consumers' purchase intention.